2023
DOI: 10.1093/jxb/erad217
|View full text |Cite
|
Sign up to set email alerts
|

The swansong of petal cell death: insights into the mechanism and regulation of ethylene-mediated flower senescence

Abstract: Flower senescence is a fundamental aspect of the developmental trajectory in flowers, occurring after the differentiation of tissues, maturation of petals and preceding the growth and development of seeds. It is accompanied by various alterations at the cytological, physiological and molecular levels, similar to other forms of programmed cell death (PCD). It involves an intricate interplay of various plant growth regulators, with ethylene being the key orchestrator in ethylene-dependent petal senescence. Petal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 138 publications
0
5
0
Order By: Relevance
“…Ethylene regulates processes like seed germination and responses to environmental stimuli [47]. The CBL-CIPK pathway affects ethylene biosynthesis and gene expression [48][49][50].…”
Section: Crosstalk Between Cbl-cipk and Ethylene Signaling Pathways I...mentioning
confidence: 99%
“…Ethylene regulates processes like seed germination and responses to environmental stimuli [47]. The CBL-CIPK pathway affects ethylene biosynthesis and gene expression [48][49][50].…”
Section: Crosstalk Between Cbl-cipk and Ethylene Signaling Pathways I...mentioning
confidence: 99%
“…The latter requires the selective and programmed elimination of groups of cells of entire organs (i.e., leaves, petals, tubers, stamina, fruits, pollen, etc.) [4][5][6][7][8][9][10][11][12] or even of the entire organism that are no longer necessary (as, for example, monocarpic plants after seed production). In some cases, PCD can be induced by a lot of occasional external factors, like environmental stresses and pathogen infections [13,14].…”
Section: Introduction Development and Pcdmentioning
confidence: 99%
“…In plants, programmed cell death (PCD) is a cell death process that is spontaneous and genetically regulated in a specific time and space through the action of endogenous developmental signals or exogenous environmental signals and is prevalent in all processes of plant growth and development [1]; for example, PCD controls root organ size and promotes optimal root growth [2]. Past studies have found that PCD was present throughout the flower opening and senescence of petals [3], and during seed germination, endosperm cells first underwent degradation and death, followed by the death of aleurone layer cells, which PCD mediated in a tightly controlled spatiotemporal pattern [4]. Furthermore, the plant PCD process is regulated by a range of signals, such as plant hormones, reactive oxygen species (ROS), calcium ions (Ca 2+ ), and nitric oxide (NO), which cross-react extensively with each other to induce PCD through different pathways [5,6].…”
Section: Introductionmentioning
confidence: 99%